Two understandings of law: Hayek vs. Schmitt in the context of Turkey. (3rd July 2017) - Şahin, Bican
ABSTRACT: The purpose of this article is to explore the consequences of following two different understandings of law for the consolidation of rule of law and democracy, provided by Friedrich von Hayek and Carl Schmitt. The context within which this exploration is carried out is the political scene of Turkey since December 2013. It is first argued that while the Hayekian understanding of law strengthens the principle of rule of law and democracy, the Schmittian understanding undermines them. Secondly, it is argued that Justice and Development Party government in Turkey has followed the Schmittian understanding of law at least since December 2013 and this in turn has undermined the rule of law and democracy in Turkey.